Value of intravoxel incoherent motion and dynamic contrast-enhanced MRI for predicting the early and short-term responses to chemoradiotherapy in nasopharyngeal carcinoma. Issue 35 (August 2016) - Hou, Jing; Yu, Xiaoping; Hu, Yin; Li, Feiping; Xiang, Wang; Wang, Lanlan; Wang, Hui; Lu, Qiang; Zhang, Zhongping; Zeng, Wenbin
Abstract : Abstract: The aim of the study was to investigate the value of intravoxel incoherent motion diffusion-weighted magnetic resonance imaging (IVIM-DWI) and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in predicting the early and short-term responses to chemoradiotherapy (CRT) in patients with nasopharyngeal carcinoma (NPC). Forty-three NPC patients underwent IVIM-DWI and DCE-MRI at baseline (pretreatment) and after the first cycle of induction chemotherapy (posttreatment). Based on whether locoregional lesions were identified, patients were divided into the residual and nonresidual groups at the end of CRT and into the good-responder and poor-responder groups 6 months after the end of CRT. The pretreatment and posttreatment IVIM-DWI parameters (ADC, D, D *, and f ) and DCE-MRI parameters ( K trans, K ep, and V e ) values and their percentage changes (Δ%) were compared between the residual and nonresidual groups and between the good-responder and poor-responder groups. None of perfusion-related parametric values derived from either DCE-MRI or IVIM-DWI showed significant differences either between the residual and nonresidual groups or between the good-responder and poor-responder groups. The nonresidual group exhibited lower pre-ADC, lower pre- D, and higher Δ% D values than did the residual group (all P   < 0.05). The good-responder group had lower pre- D and pre-ADC values than did the poor-responder group (both P   < 0.05). Based on receiver operating characteristic (ROC) curve analysis, pre- D had the highest area under the curve in predicting both the early and short-term responses to CRT for NPC patients (0.817 and 0.854, respectively). IVIM-DWI is more valuable than DCE-MRI in predicting the early and short-term response to CRT for NPC, and furthermore diffusion-related IVIM-DWI parameters (pre-ADC, pre- D, and Δ% D ) are more powerful than perfusion-related parameters derived from both IVIM-DWI and DCE-MRI.